Mental health problems and coping strategy among pulmonary resident physicians during the COVID-19 pandemic in a tertiary respiratory hospital in Indonesia: a serial cross-sectional study (Medical Journal of Indonesia, 2022)
BACKGROUND Pulmonary resident physicians are part of the frontline workers for COVID-19 in the hospital and might require a suitable coping strategy to manage stress. Here, we described their mental health status and coping strategy during the COVID-19 pandemic. METHODS A cohort study was done to evaluate stress, anxiety, depression, and coping strategies among pulmonary resident physicians in a tertiary referral hospital. Questionnaires were administered in 4 time points between August 2020 and June 2021. The DASS-21 questionnaire measured depression, anxiety, and stress, while Brief COPE instrument qualified the coping strategy. RESULTS The total respondents who filled the questionnaire in 4 time points in August 2020, October 2020, February 2021, and June 2021 were 60, 93, 96, and 94 resident physicians with mean stress levels of 4.3, 6.1, 5.4, and 6.3, respectively. Depression, stress, and anxiety were less frequent during the study period, mostly mild or moderate. However, moderate anxiety slightly increased in June 2021 when the pandemic reached its peak. Most of them (95.8%) had effective coping strategies related to religious beliefs. CONCLUSIONS Effective coping strategies might preserve the pulmonary resident physicians’ mental health during the pandemic. Furthermore, the sociodemographic and cultural background might affect the coping strategy. Practicing religion and praying or meditating might be essential factors in coping with psychological distress and a key to adapt to the COVID-19 pandemic.